Analisis Minat Belajar Siswa Menggunakan Media Pembelajaran E-comic Aritmatika Sosial Masa Pandemi Covid-19 - BatuBara, Yosse Andreas; Zetriuslita, Zetriuslita; Dahlia, Agus; Effendi, Leo Adhar (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
The Covid-19 pandemic has become a trending topic of conversation for the past year until now, this pandemic has changed various aspects of human life today, especially in the world of education. This causes students' failure to understand mathematical concepts and students' lack of interest in learning. This study aims to describe students' learning interest in the use of E-comic media in social arithmetic material during the Covid-19 pandemic. This research is a descriptive quantitative research. The sample of the research was the seventh grade students of SMP which consisted of 15 students who were taken randomly. The instrument used in this study is a non-test instrument in the form of a student learning interest questionnaire distributed using Google Form in social arithmetic learning using E-comic which consists of 20 statements as a reference to determine students' interest in learning in the use of E-comic media. The data analysis technique used in this research is quantitative descriptive analysis. The results of this study indicate that the use of E-comic learning media is effective on student learning interest during the Covid-19 pandemic with the percentage results80.67% classified as very high criteria. So that the E-comic learning media is very effectively used as a medium for learning mathematics to increase student interest in learning during the Covid-19 pandemic.Keywords: analysis, E-comic, social arithmetic, covid-1 pandemicÂ